Synthesis Of Palladium(Ii) Diimine Complexes And The Hydrolysis Of Α-Diimine Ligand = (Sintesis Kompleks Diimina Palladium(II) dan Hidrolisis Ligan α-Diimina) - Tay, Meng Guan; Hui, Suzie Chin Kuan; Liu, Zhi-Qiang (The Malaysian Analytical Sciences Society, 2019)
The reactions of dichlorobis(acetonitrile)palladium(II) precursors with 1,4-diaza-1,3-butadienes (α-diimine) give rise to the products (1,4-bis(4-methoxyphenyl)-1,4-diaza-1,3-butadiene)dichloropalladium(II) (2a) and (1,4-bis(4-methylphenyl)-1,4- diaza-1,3- tadiene)dichloropalladium(II) (2b), as deduced from elemental analysis, FTIR, and UV-Vis. Both complexes are soluble in dimethylformamide and single crystals were collected for an X-ray crystallographic study. Based on the crystallographic data, complex 2a is crystalized in a monoclinic system with P21 /c space group. The Pd-N bond lengths for Pd01-N004 and Pd01-N005 are 2.045(2) and 2.033(2) Å, respectively. Surprisingly, when complex 2b dissolved in dimethylformamide, 4-methylaniline was produced from the hydrolysis of the α-diimine ligand 1b, therefore transdichloridobis(4-methylaniline-κN)-palladium(II) (2c) was formed as confirmed, by crystallographic data. Complex 2c is crystallized in a triclinic system with P 21 /b 21 /c 21 /a (Pbca) space group. The bond lengths of Pd-N are 2.050(3) Å and Pd-Cl is 2.318(8) Å. There are weak intermolecular N-H···Cl hydrogen bonds, that are responsible for the packing of the molecules in formation.